How language environment, age, and cognitive capacity support the bilingual development of Syrian refugee children recently arrived in Canada. (15th November 2020) - Paradis, Johanne; Soto-Corominas, Adriana; Chen, Xi; Gottardo, Alexandra
Abstract: Research on the bilingual development of refugee children is limited, despite this group having distinct characteristics and migration experiences that could impact language development. This study examined the role of language environment factors, alongside age and cognitive factors, in shaping the Arabic as a first/heritage language and English as a second language of recently arrived Syrian refugee children in Canada ( N = 133; mean age = 9 years old; mean family residency = 23 months). We found that Arabic was the primary home language with some English use among siblings. Children did not engage frequently in language-rich activities in either language, especially not literacy activities in Arabic. Parent education levels were low: most had primary school only. Hierarchical regression models revealed that stronger nonverbal reasoning skills, more exposure to English at school, more sibling interaction in English, more frequent engagement in language-rich activities in English, and higher maternal and paternal education were associated with larger English vocabularies and greater accuracy with verb morphology. Arabic vocabulary and morphological abilities were predicted by older age (i.e., more first/heritage language exposure), stronger nonverbal reasoning skills and maternal education. We conclude that proximal environment factors, like language use at home and richness, accounted for more variance in the second language than the first/heritage language, but parent factors accounted for variance in both languages.